надо решение а не ответ
Номер 57 и 58


надо решение а не ответ Номер 57 и 58

лалалалад1 лалалалад1    3   07.06.2020 10:34    1

Ответы
diekaaaaa diekaaaaa  15.10.2020 13:19

57) -3(x-3)/4(x-3)= -3/4

58) (2x(x-6)+2x(x+6))/(x^2-36)= (2x^2-12x+2x^2+12x)/(x^2-36)= 4x^2(x^2-36)

ПОКАЗАТЬ ОТВЕТЫ
Dimas1694 Dimas1694  15.10.2020 13:19

57) 3(3-x)/4(x-3) = -3(x-3)/4(x-3) = -3/4

58)

2x/x+6 + 2x/x-6 = 2x(x-6)/(x+6)(x-6) + 2x(x+6)/(x+6)(x-6) = 2x²-12x+2x²+12x/x²-36 = 4x²/x²-36

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра